The Effect Of Using Quick Teaching Program According to Kinetic and Social Intelligence On Some Basic Skills In Tennis Players Aged 11 – 12 - Jalal, Ali; Abdul Azeez, Tamador (Journal of Physical Education, 2019)
The study aimed at designing a teaching program using styles and aids for quick learning according to social and kinetic intelligences on learning some basic skills in tennis for players aged 11 – 12 years old as well as identifying differences between pre and posttests for experimental and controlling groups in some basic skills in tennis for players aged 11 – 12 years old.  The researcher used the experimental method. The subjects were (12) beginner tennis players aged 11 – 12 years old from Al – Jadria Tennis Academy. They were divided equally into two groups.  The researcher conducted few tests including Hensely for performance level and Atenza for evaluating serve skill performance and concentration. The teaching program was applied that consisted of two parts; the teaching part and application part. The teaching program lasted for 12 weeks with three teaching sessions per week. The data was collected and treated using proper statistical operations. The researchers concluded that quick learning is more effective in developing basic skills in tennis forehand and backhand and serve for kinetic intelligent compared to social intelligent.